"I need to go to the gym": Exploring the use of rational emotive behaviour therapy upon exercise addiction, irrational and rational beliefs. Issue 2 (August 2018) - Outar, L.; Turner, M.J.; Wood, A.G.; Lowry, R.
Abstract: Extant research suggests that irrational and rational beliefs may play an important role in both substance and behavioural addictions. However, the influence of irrational and rational beliefs pertaining to exercise addiction has yet to be investigated. Rational emotive behaviour therapy (REBT) is a cognitive-behavioural approach that provides a theoretical framework to identify and change irrational beliefs through cognitive restructuring and endorsing rational beliefs. The principal aim of the current study is to examine the effectiveness of a one-to-one REBT programme in decreasing irrational beliefs and exercise addiction symptoms, and increasing unconditional self-acceptance, in three male exercisers. The exercisers present high symptoms of exercise addiction, and high irrational beliefs. A single-case, staggered multiple-baseline across participant A-B design is used in the current study to examine the effects of a six-week REBT program comprising six 45 min one-to-one counselling sessions and 5 homework assignments. Visual and statistical analyses and social validation data indicate strong reductions in low-frustration tolerance, composite irrational beliefs, and exercise addiction from pre- to intervention phase. In addition, all participants report increased unconditional self-acceptance. This is the first study to report the effects of REBT in an exercise population, and the first to demonstrate that exercise addiction symptoms can be attenuated using REBT. This study supports literature suggesting that irrational and rational beliefs are an important mechanism in exercise addiction and provides important implications for the development of its treatment.